Synergy effect of Sr and rhBMP-2: A potential solution to osteolysis caused by rhBMP-2. (November 2020) - Li, Zhonghai; Wang, Shiyuan; Xu, Gang; Hu, Xiantong; Han, Liwei; Zhao, Yantao
Abstract: As an approach to enhance autogenous bone grafting, the fusion rate of recombinant human bone morphogenetic protein-2 (rhBMP-2) is close to 100%, which is significantly higher than other bone graft methods. However, there are some obvious problems in applying rhBMP-2 clinically. Among them, early endplate osteolysis frequently occurs in the lumbar interbody fusion, which readily leads to cage subsidence or shift, thus influencing clinical effects. Moreover, robust bone formation activity and serious osteolysis coexist. What is the internal mechanism? How do we solve this problem? Strontium (Sr) is now widely used for the treatment of osteoporosis. It elicits a double effect in that it simultaneously enhances bone formation and inhibits bone resorption. We propose that Sr might be a solution for osteolysis induced by rhBMP-2 in spinal interbody fusion. Whether this synergistic effect leads to new metabolic pathway activation remains to be explored. Clarifying the synergistic effect and mechanism will be of great importance in improving both the osteogenic effect and reducing the dose amount of rhBMP-2, as well as corresponding costs.